Transposable elements in the transcriptome of the velvetbean caterpillar Anticarsia gemmatalis Hübner, 1818 (Lepidoptera: Erebidae) - Pezenti, Larissa Forim; Dionisio, Jaqueline Fernanda; Sosa-Gómez, Daniel Ricardo; de Souza, Rogério Fernandes; da Rosa, Renata (Genome, 2023)
Transposable elements (TEs) are DNA sequences that possess the ability to move from one genomic location to another. These sequences contribute to a significant fraction of the genomes of most eukaryotes and can impact their architecture and regulation. In this paper, we present the first data related to the identification and characterization of TEs present in the transcriptome of Anticarsia gemmatalis. Approximately, 835 transcripts showed significant similarity to TEs and (or) characteristic domains. Retrotransposons accounted for 71.2% (595 sequences) of the identified elements, while DNA transposons were less abundant, with 240 annotations (28.8%). TEs were classified into 30 superfamilies, with SINE3/5S and Gypsy being the most abundant. Based on the sequences of TEs found in the transcriptome, we were able to locate conserved regions in the chromosomes of this species. The analysis of differential expression of TEs in susceptible and resistant strains, challenged and not challenged with Bacillus thuringiensis ( Bt) from in silico analysis, indicated that exposure to Bt can regulate the transcription of mobile genetic elements in the velvetbean caterpillar. Thus, these data contribute significantly to the knowledge of the structure and composition of these elements in the genome of this species, and suggest the role of stress on their expression.